Targeted use of umbilical cord matrix stem cells for cancer therapy - Rachakatla, Rajashekar (Kansas State University, 2008)
Umbilical cord matrix stem (UCMS) cells are derived from Wharton's jelly and have been shown to express genes characteristic of primitive stem cells. They can be isolated in large numbers in a short time and thus potentially represent an abundant source of cells for therapeutic use. We investigated the migratory nature of human UCMS cells towards MDA 231 human breast carcinoma cells in an in vitro model of cell migration; UCMS cells cultured with or without MDA 231 cells for 24 hours. Next, we evaluated the effect of chemokines, stromal derived factor 1 (SDF-1) and vascular endothelial growth factor (VEGF) on human UCMS cells by treating with increasing doses of SDF-1 and VEGF. UCMS cells were found to migrate towards MDA 231 cells in a dose dependent manner. Both SDF-1 and VEGF induced migration of UCMS cells in a dose dependent manner. These results suggest that MDA 231 cells might be releasing chemokine factors, such as SDF-1 and VEGF, which promote UCMS cell migration towards the tumor cells in vitro. Stem cells that migrate to tumors may allow targeted delivery of therapeutic agents that otherwise may have severe side effects. To evaluate the selective engraftment and therapeutic efficiency of human UCMS cells that were engineered to express interferon beta (UCMS-IFN-beta) MDA 231 cells (2,000,000) were intravenously injected into severe combined immune deficient (SCID) mice, followed by three weekly intravenous injections of fluorescently labeled UCMS-IFN-beta cells (500,000). To evaluate the synergistic effect of 5-Fluorouracil (5-FU) and IFN-beta, MDA 231 cells were intravenously injected into SCID mice, followed by three weekly intravenous injections of fluorescently labeled UCMS-IFN-beta cells and three weekly intra peritoneal injections of 5-FU. In both of the above experiments, mice were euthanized one week after the last UCMS cell transplant and lung weights were compared to the controls to determine the differences in tumor burden. After transplantation of UCMS-IFN-beta cells into MDA 231 tumor-bearing mice, UCMS cells were found near or within metastatic lung tumors but not in other tissues, and in these animals, the lung weight was significantly less than MDA 231 tumor-bearing animals that received saline injections. Histologically, there was significant reduction in the tumor area in MDA 231 tumor bearing lungs after UCMS-IFN-beta treatment. When 5-FU was given along with UCMS-IFN-beta cells, there was further reduction in tumor area. These results indicate that UCMS cells can potentially be used for targeted delivery of cancer therapeutics.
Keywords: Stem cells; Tumors; Interferon beta; 5-FU; Biology, Animal Physiology (0433)